Roma Hukukunda Korkutma (Metus) - (:unkn) unknown (My University, 2017)
Modern hukuku etkileyen bir Roma Hukuku kavramı daha: Metus Korkutmaya (metus), yani iradenin oluşumundaki bozukluğa rağmen ius civile\'ye göre geçerli kabul edilen hukuki muamele, yine praetor\'ların adaleti tesis etme çabaları sonucunda dikkate alınmıştır. Bu çalışmamızda metus kavramının Roma Hukukundaki gelişimini ve praetor\'ların korkutmaya maruz kalan kişiyi hakkaniyet gereği koruma yollarını inceledik.s

Another Roman law concept which influences the modern law: Metus The legal action which had, according to ius civile, been accepted as valid despite duress (metus), i.e., a defect in the formation of the will, was considered as a result of the praetors\' attempts to establish justice. In this article, we have analyzed the evolution of metus as a concept in Roman law and the methods developed by the praetors to protect the person exposed to duress.
Duress in Roman Law (Metus)
Keywords: Hukuk